Antiarthritic activity of synthesized silver nanoparticles from aqueous extract of Moringa concanensis Nimmo leaves against FCA induced rheumatic arthritis in rats - Ramaswamy, Malathi; Solaimuthu, Chandrasekar; Duraikannu, Sivakumar (Journal of Drug Delivery and Therapeutics, 2019)
Background and Objective: The rheumatoid arthritis is autoimmune disease and it is a major health issues among the peoples in worldwide. People affected by rheumatism have double risk of heart disease, lungs and chest infections, which causes 10-20% of deaths in individuals. The present research work was aimed to evaluate the antiarthritic potential of synthesized silver nanoparticles from the aqueous extract of M.concanensis leaves.Material and Methods: The arthritis was induced by complete freund’s adjuvant method and the rats was treated with synthesized silver nanoparticles from aqueous extract of M.concanensis leaves. The body weight, paw volume, hematological parameters, liver function marker enzymes and the renal function markers of the arthritic rats and nanoparticles treated rats was analyzed by the standard methods.Results: The results of the present study were made the new findings in antiarthritic activity of silver nanoparticles from M.concanensis leaves. The nanoparticles showed a noteworthy antiarthritic activity against FCA induced rheumatoid arthritis in experimental rats.Conclusion: Based on the above results, it was concluded as the present work are states the better understand on the antiarthritic activity of silver nanoparticles of Moringa concanensis Nimmo leaves.